Providing the minds of the out-of-the-box digitalization as the basic component of the information culture of the teacher - Pistunova, Tetiana; Slabko, Volodymyr; Averina, Kateryna; Romanchenko, Inna; Babakina, Oksana; Vidomenko, Oksana (My University, 2021)
The article is devoted to questions of formation and development of the higher vocational school of the information competence defined as a basic component of information culture. The author of the provisions which account in student teaching will promote realization of an effective technique of system application of information and communication technologies and achievement of the objectives of high school education locate.
Keywords: digitalization; distance education; higher education; local network communications; кафедра економіки і права